Role of Probiotics in Stimulating the Immune System in Viral Respiratory Tract Infections: A Narrative Review - Lehtoranta, Liisa (Nutrients, 2020)
Viral respiratory tract infection (RTI) is the most frequent cause of infectious illnesses including the common cold. Pharmacological solutions for treating or preventing viral RTIs are so far limited and thus several self-care products are available in the market. Some dietary supplements such as probiotics have been shown to modulate immune system function and their role in reducing the risk and the course of RTIs has been investigated extensively within the past decade. However, the mechanism of action and the efficacy of probiotics against viral RTIs remains unclear. We searched PubMed, Google Scholar, and Web of Knowledge for pre-clinical and clinical studies investigating the effect of probiotics on respiratory virus infections, immune response, and the course of upper and lower respiratory tract illness. The literature summarized in this narrative review points out that specific probiotic strains seem effective in pre-clinical models, through stimulating the immune system and inhibiting viral replication. Clinical studies indicate variable efficacy on upper respiratory illnesses and lack proof of diagnosed viral infections. However, meta-analyses of clinical studies indicate that probiotics could be beneficial in upper respiratory illnesses without specific etiology. Further studies aiming at discovering the mechanisms of action of probiotics and clinical efficacy are warranted.